2019
DOI: 10.2478/jeb-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Migration Following the EU Enlargement: A Panel Data Analysis

Abstract: The Eastern enlargements of the European Union (EU) since the early 2000s have included post-transitional economies at a lower level of development than the existing member states and thus, have significantly affected the East-West migration flows and labour markets on both sides. This has provided a distinctive opportunity to study the effects of liberalisation and to identify economic factors leading to migration flows with the purpose of enabling better estimations of future migration trends. In this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
10
0
2
Order By: Relevance
“…First, an overvalued exchange rate in the host country is positively correlated with migration, not negatively. Second, the sign of the income variable switches so that poorer EE countries send fewer emigrants out, not more, and this result is consistent with that of Franc, Časni, and Barišić (2019). Neither autocracy nor conflict in the origin country appears to matter for this subsample.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…First, an overvalued exchange rate in the host country is positively correlated with migration, not negatively. Second, the sign of the income variable switches so that poorer EE countries send fewer emigrants out, not more, and this result is consistent with that of Franc, Časni, and Barišić (2019). Neither autocracy nor conflict in the origin country appears to matter for this subsample.…”
Section: Resultssupporting
confidence: 71%
“…He develops a model of migration choice that predicts a higher emigration rate in response to a higher mean income in the host country, a lower mean income in the origin country, a lower cost of migration, and a greater reward in the host country for the migrant's specific demographic characteristics. Franc, Časni, and Barišić (2019) studied the migration that resulted from the enlargement of the European Union, as citizens of Eastern Europe moved to Western Europe, and he framed migration as a result of both push and pull factors. He found that this migration rose from higher per-capita GDP in the host country, but also rose from higher income in the origin country.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Quite a few recent articles analyse the reasons and the effects of international emigration from the developing countries to the rich ones (Franc et al, 2019;Phyo et al, 2019;Ivlevs et al, 2019). However, just a few pieces of research investigate whether inequality within one country is a cause for emigration.…”
Section: Background: Income Inequality Subjective Well-being and Emmentioning
confidence: 99%
“…Another aspect is associated with youth migration. Some studies show that youngsters are more likely to immigrate to countries with growing GDP (Franc et al, 2019). This trend is a consequence of one of the fundamental EU principles -the free movement of persons.…”
Section: Introductionmentioning
confidence: 99%